Removal of copper from aqueous solutions using reactive extraction - Datta, Arghya (My University, 2015)
The thesis is concentrated on the use of reactive extraction for purification of aqueous streams containing Copper(II) ions. Dissolved Cu2+ ions are removed from the aqueous solution with the help of TBP as the reactive extractant. Benzene is used as the diluent to decrease the viscosity of the TBP. The effect of various parameters on removal percentage, namely, initial copper concentration, extractant percentage in extractant-dilutent mixture, O/A ratio, pH and temperature were studied. A percentage extraction of 98% was obtained under the optimized conditions ( initial Cu2+ concentration =20ppm, O/A ratio = 3:1, pH = 6,temperature = 25°C, extractant concentration = 1.825mol L-1). A two stage stripping process was also undertaken at 70°C to strip the aqueous solution received after the extraction tests and to reuse the clean extractant solvent for subsequent reactive extraction tests. 4N H2SO4 was used as the stripping agent. Thermodynamic analysis was done for the process which inferred that the process is exothermic and is favourable at low temperature and also forms a stable Cu-TBP complex.
M.Tech-Chemical-Thesis
Keywords: Reactive extraction; Stripping; Thermodynamic Analysis; chemical engineering; ched